Use of Ceftazidime-avibactam for the Treatment of Extensively drug-resistant or Pan drug-resistant Klebsiella pneumoniae in Neonates and Children <5 Years of Age. Issue 8 (August 2019) - Iosifidis, Elias; Chorafa, Elisavet; Agakidou, Eleni; Kontou, Aggeliki; Violaki, Asimina; Volakli, Eleni; Christou, Eleni-Ifigeneia; Zarras, Charalampos; Drossou-Agakidou, Vassiliki; Sdougka, Maria; Roilides, Emmanuel
Abstract : Background: Emergence of extensively drug-resistant (XDR) or pan drug-resistant (PDR) Enterobacteriaceae is a major public threat especially for young patients. Treatment options for these bacteria are extremely limited with no safety data existing for neonates and children. Ceftazidime-avibactam has activity against Gram-negative bacteria producing Klebsiella pneumoniae carbapenemase, but virtually no data exist on its use in neonatal and pediatric patients. Methods: We present a single-center case series of neonates and children <5 years treated with ceftazidime-avibactam for XDR or PDR K. pneumoniae infections until August 2018. Medical records of patients who received ceftazidime-avibactam for at least 2 days (6 doses) were reviewed. Clinical, laboratory and microbiologic data were collected using a prestructured form. Adverse events and clinical/microbiologic responses and 15- and 30-day outcome were assessed. Results: In our case series, 8 patients (median age 53 days, range from 13 days to 4.5 years) received 9 courses of ceftazidime-avibactam at a dose of 62.5 mg/kg q8h for suspected or proven XDR/PDR K. pneumoniae infections including bloodstream infections (8 courses), central nervous system infections (2 courses) and urinary tract infection (1 course). All patients were critically ill and received other antibiotics prior and concomitantly with the administration of ceftazidime-avibactam. There was no treatment discontinuation due to adverse events. Clinical and microbiologic responses occurred in all patients, and no patient died by day 30. Conclusions: Administration of ceftazidime-avibactam appears to be well tolerated and efficacious against in vitro susceptible XDR or PDR Enterobacteriaceae without being associated with significant adverse events. Abstract : Supplemental Digital Content is available in the text.